Distribution of the Silurian brachiopod genus Atrypoidea, and its first report in the Chejiaba Formation (upper Ludlow), Guangyuan, South China. (January 2023) - Chen, Di; Huang, Bing; Rong, Jiayu
Abstract: Atrypoidea is a Silurian smooth atrypide with a worldwide distribution and high species-level diversity especially during Ludlow to Prídolí. In this study, the occurrences of 67 species, 14 subspecies, and 23 forma, cf., aff., or var. species are summarized. Among them, Atrypoidea recta from Aeronian of Siberia is the earliest known occurrence of this genus, while Atrypoidea elatior or Atrypoidea polaris modica from upper Prídolí strata of the Czech Republic and China, respectively, should be the youngest species. No valid Devonian occurrence of Atrypoidea has been recorded due to absence of convincing identification or poor stratigraphic information. The rapid evolution and cosmopolitan nature of Atrypoidea allow some species to be used as index fossils for strata of Ludlow and Prídolí in South China. The age of the Chejiaba Formation in Guangyuan, Sichuan Province, South China, has been clarified based on the occurrence of Atrypoidea . Specimens from this locality, which are preserved in situ, are described herein and illustrated with reconstruction of life style for the first time.